Androgen receptor‐interacting protein HSPBAP1 facilitates growth of prostate cancer cells in androgen‐deficient conditions. Issue 11 (20th November 2014) - Saeed, Khalid; Östling, Päivi; Björkman, Mari; Mirtti, Tuomas; Alanen, Kalle; Vesterinen, Tiina; Sankila, Anna; Lundin, Johan; Lundin, Mikael; Rannikko, Antti; Nordling, Stig; Mpindi, John‐Patrick; et al.
<x xml:space="preserve">Abstract</x> Hormonal therapies targeting androgen receptor (AR) are effective in prostate cancer (PCa), but often the cancers progress to fatal castrate‐resistant disease. Improved understanding of the cellular events during androgen deprivation would help to identify survival and stress pathways whose inhibition could synergize with androgen deprivation. Toward this aim, we performed an RNAi screen on 2, 068 genes, including kinases, phosphatases, epigenetic enzymes and other druggable gene targets. High‐content cell spot microarray (CSMA) screen was performed in VCaP cells in the presence and absence of androgens with detection of Ki67 and cleaved ADP‐ribose polymerase (cPARP) as assays for cell proliferation and apoptosis. Thirty‐nine candidate genes were identified, whose silencing inhibited proliferation or induced apoptosis of VCaP cells exclusively under androgen‐deprived conditions. One of the candidates, HSPB (heat shock 27 kDa)‐associated protein 1 (HSPBAP1), was confirmed to be highly expressed in tumor samples and its mRNA expression levels increased with the Gleason grade. We found that strong HSPBAP1 immunohistochemical staining (IHC) was associated with shorter disease‐specific survival of PCa patients compared with negative to moderate staining. Furthermore, we demonstrate that HSPBAP1 interacts with AR in the nucleus of PCa cells specifically during androgen‐deprived conditions, occupies chromatin at PSA/klk3 and TMPRSS2/tmprss2 enhancers and regulates their expression. In conclusion, we suggest that HSPBAP1 aids in sustaining cell viability by maintaining AR signaling during androgen‐deprived conditions.